Road Vehicle Automation 5 - Meyer, Gereon; Beiker, Sven.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This is the fifth volume of a sub series on Road Vehicle Automation published within the Lecture Notes in Mobility. Like in previous editions, scholars, engineers and analysts from all around the world have contributed chapters covering human factors, ethical, legal, energy and technology aspects related to automated vehicles, as well as transportation infrastructure and public planning. The book is based on the Automated Vehicles Symposium which was hosted by the Transportation Research Board (TRB) and the Association for Unmanned Vehicle Systems International (AUVSI) in San Francisco, California (USA) in July 2017.
Public Sector Activities -- Human Factors and Challenges -- Technology, Energy and Business Perspectives -- Vehicle Systems and Technologies Development -- Transportation Infrastructure and Planning.
Keywords: Automotive engineering; Control engineering; Robotics; Automation; Artificial intelligence; Transportation engineering; Traffic engineering; Technological innovations; Automotive Engineering; Control, Robotics, Automation; Artificial Intelligence; Transportation Technology and Traffic Engineering; Innovation and Technology Management